2017
DOI: 10.1007/s11199-017-0826-z
|View full text |Cite
|
Sign up to set email alerts
|

The Problematization of Sexuality among Women Living with HIV and a New Feminist Approach for Understanding and Enhancing Women’s Sexual Lives

Abstract: In the context of HIV, women's sexual rights and sexual autonomy are important but frequently overlooked and violated. Guided by community voices, feminist theories, and qualitative empirical research, we reviewed two decades of global quantitative research on sexuality among women living with HIV. In the 32 studies we found, conducted in 25 countries and composed mostly of cis-gender heterosexual women, sexuality was narrowly constructed as sexual behaviours involving risk (namely, penetration) and physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 199 publications
(306 reference statements)
3
30
0
Order By: Relevance
“…Our data, from the contemporary antiretroviral therapy era, suggest that the impact of HIV diagnosis on sexual function endures longer than previously described. We found no association between sexual function and nadir CD4 count, current CD4 count or HIV viral load, in keeping with other studies (Carter et al, 2017). It is therefore likely that multidimensional contextual factors play an important role in sexual well-being including the emotional impact of HIV diagnosis, experiences of trauma and violence, age, HIV-related stigma, and concerns about HIV transmission (Carter et al, 2017), many of which we did not measure in the PRIME Study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data, from the contemporary antiretroviral therapy era, suggest that the impact of HIV diagnosis on sexual function endures longer than previously described. We found no association between sexual function and nadir CD4 count, current CD4 count or HIV viral load, in keeping with other studies (Carter et al, 2017). It is therefore likely that multidimensional contextual factors play an important role in sexual well-being including the emotional impact of HIV diagnosis, experiences of trauma and violence, age, HIV-related stigma, and concerns about HIV transmission (Carter et al, 2017), many of which we did not measure in the PRIME Study.…”
Section: Discussionsupporting
confidence: 86%
“…It is unsurprising that women living with HIV are more likely to seek help within sexual health services as in many parts of the UK, HIV and sexual health services are provided within the same department affording women the opportunity to have sexual health issues addressed. The effects of living with HIV on women's sexual well-being are widely recognised (Carter et al, 2017). We found an association between lower sexual function and having been diagnosed with HIV for ≥20 years.…”
Section: Discussionmentioning
confidence: 59%
“…Although there has been increased access to ART, studies examining sexuality and reproduction for women living with HIV still show that HIV impacts sexuality and reproduction negatively (Carter et al, 2017a; Greene, Ion, Kwaramba, Smith, & Loutfy, 2015; Rahangdale et al, 2014). Women with HIV therefore face unique challenges, such as in partner relationships, sexual satisfaction and childbearing (Bharat & Mahendra, 2007; Carter et al, 2013; Florence et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, a Swedish inductive interview study examining seven HIV-positive women’s sexuality showed that fear of transmitting HIV to one’s partner is highly present (Norwald, Holmström, & Plantin, 2017). In order to support the health and well-being of women living with HIV, health care professionals need access to a solid knowledge base about issues related to HIV, sexuality and childbearing (Carter et al, 2017a; Shapiro & Ray, 2007). There is still insufficient knowledge regarding what sexuality and childbearing means to women living with HIV in a Swedish context.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with the increasing use of pre-exposure prophylaxis (PrEP) by HIV negative sexual partners of PLWH [9][10][11], these developments mean that earlier research on the impact on sexual functioning and adjustment following HIV diagnosis may no longer be applicable. Feminist and sexual rights perspectives have been applied to theorise ways to promote the sexual well-being of women with HIV [12]. Yet, there is currently no model of factors which promote sexual adjustment to HIV to guide further research and intervention into this important aspect of quality of life for PLWH.…”
Section: Introductionmentioning
confidence: 99%